How gender and low mental health literacy are related to unmet need for mental healthcare: a cross-sectional population-based study in Sweden - Sara Blom; Frida Lindh; Andreas Lundin; Bo Burström; Gunnel Hensing; Jesper Löve (BMC, 2024)
Abstract Background Men are more likely to have unmet need for mental healthcare than women. However, an under-investigated aspect of the gender difference is the role of mental health literacy. This study investigated how combinations of gender and mental health literacy were related to two indicators of unmet need: not perceiving a need for mental healthcare despite poor mental health, and refraining from seeking mental healthcare. Methods This cross-sectional study was based on a questionnaire sent to a general population sample, aged 16-84 years, in Stockholm County, Sweden, in 2019. Of the 1863 respondents (38%), 1563 were included (≥18 years). The sample was stratified into four groups, men and women with low or high mental health literacy, using the third quartile of the Mental Health Knowledge Schedule. The likelihood of not perceiving a need for mental healthcare and refraining from seeking mental healthcare, at any time in life, were investigated by calculating odds ratios with 95% confidence intervals. Results Men with low mental health literacy were most likely to not perceive a need for mental healthcare, also when adjusting for age, education, and poor mental health (OR 5.3, 95% CI 3.6-7.7), and to refrain from seeking mental healthcare, also when adjusting for age and education (OR 3.3, 95% CI 1.7-6.4), followed by men with high mental health literacy (OR 1.9, 95% CI 1.5-2.4, and OR 1.5, 95% CI 1.0-2.2) and women with low mental health literacy (OR 1.9, 95% CI 1.2-2.9, and OR 2.1, 95% CI 1.1-3.9). Women with high mental health literacy were least likely (reference group). Conclusion The results show differences in the likelihood of unmet need for mental healthcare based on combinations of gender and mental health literacy level, with men having low mental health literacy being most at risk, and women with high mental health literacy being least at risk. This challenges generalisations of a gender difference in unmet need by showing heterogeneity among men and women based on mental health literacy. Men with low mental health literacy may be particularly in need of targeted interventions to reduce potential individual and societal consequences of their unmet need.